Drain Hole Installation Design in an Open Coal Mine - Cahyadi, Tedy Agung; Fadlil, Doni Firdaus; Titisariwati, Indun; Hartono, Hartono; Nursanto, Edy; Ansori, Muhammad Iqbal; Anggoro, Hengky (Journal TECHNO, 2021)
The presence of groundwater on the mine slopes can disturb the stability of the slope. High groundwater can increase pore pressure which affects the amount of load on the mine slope. In order to lower the groundwater level, it is necessary to have drainage holes to drain water naturally. This study aims to design a horizontal drain installation so that it can lower the groundwater table. The results of this study indicate the existence of an aquifer in the form of sandstones. In this aquifer horizontal drains will be installed. The results of this study are in the form of horizontal drains installation design, namely, the location of the installation of the horizontal drain, the diameter of the boreholes, the distance between the boreholes, the length of the horizontal drains installation pipe, and the angle of inclination of the installation of the horizontal drains.